(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Supplementation of agro-industrial by-products to improve ruminant production both in quantity and quality during period of feed scarcity is important for maintenance and increased productivity. This study investigated the performance of ewe-lamb and milk composition of West African Dwarf (WAD) ewe fed differently processed orange peel diets. The oestrus cycle of ewes was synchronized with prostaglandin injection. Milk collection was done after lambing for 12 weeks. The treatment were; control diet (0% OP), 15% unfermented orange peels (15% UFOP) and 15% fermented orange (15% FOP). Twenty-four (24) ewes with average weight of 14.27±0.47 kg was allotted to three treatment groups in a Completely Randomized Design. The experiment investigated the phytochemical, ewe-lamb performance, milk composition and milk yield of WAD dams fed UFOP and FOP diets. Data collected were analyzed using One-way Analysis of Variance. Results revealed that tannin, oxalate and saponin in FOP were 23.80 g/kg, 201.20 g/kg and 73.10 g/kg while 14.50 g/kg, 164.50 g/kg and 45.60 g/kg for UFOP. Weaning weight, weight gain and daily weight gain decreased (p<0.05) in lambs fed 15% UFOP and 15% FOP supplementation compared to the control. Partial milk yield increased (p<0.05) in 0% OP compared to the other treatment groups. Lactose, protein, milk density and solid particle were elevated (p<0.05) in 15% UFOP supplementation. The study concluded that supplementation of 15% UFOP and 15% FOP improved ewe-lamb weight, chemical properties of milk.